Impact of SMS-Based Agricultural Information on Indian Farmers - Fafchamps, Marcel (Oxford University Press on behalf of the World Bank, 2014)
This study estimates the benefits that Indian farmers derive from market and weather information delivered to their mobile phones by a commercial service called Reuters Market Light (RML). We conduct a controlled randomized experiment in 100 villages of Maharashtra. Treated farmers associate RML information with a number of decisions they have made, and we find some evidence that treatment affected spatial arbitrage and crop grading. But the magnitude of these effects is small. We find no statistically significant average effect of treatment on the price received by farmers, crop value-added, crop losses resulting from rainstorms, or the likelihood of changing crop varieties and cultivation practices. Although disappointing, these results are in line with the market take-up rate of the RML service in the study districts, which shows small numbers of clients in aggregate and a relative stagnation in take-up over the study period.